Islamic Ethical Frameworks and Institutional Trust: Empirical Analysis of Moral Economy Practices in Muslim Community Development - Nadiyah Nadiyah; Inawati Mohammad Jainie Jarajap; Diana Rahmi; Sa'adah Sa'adah; Farihatni Mulyati (Fakultas Syariah UIN Antasari, 2026)
Contemporary Muslim societies face a critical gap between Islamic ethical principles and actual institutional practices in community development. This situation has intensified demand for values-driven financial and organizational systems that move beyond formal Shariah compliance to promote justice, sustainability, and social welfare. Recent institutional transformations indicate that Islamic organizations are increasingly embedding ethical frameworks into their operations, yet empirical validation is still needed to confirm whether explicit moral economy mechanisms can strengthen institutional trust. In this context, Maqasid al-Shariah offers a relevant framework for redesigning governance structures and social finance instruments. Grounded in Maqasid al-Shariah, which prioritizes the protection of faith, life, intellect, lineage, and wealth, this study examines whether institutional trust in Muslim community development organizations increases when explicit Islamic ethical frameworks guide organizational practice. It also investigates how such frameworks are institutionalized, how moral economy practices relate to trust levels, and what mechanisms strengthen stakeholder confidence. This study employs a mixed-methods design combining qualitative case studies and quantitative survey analysis. Primary data were collected through 25 in-depth interviews with organizational leaders, Shariah scholars, and community members, along with focus group discussions in three Indonesian regions. Secondary data include organizational documents, financial reports, and governance records. Quantitative data from 320 community members were analyzed using structured questionnaires and exploratory factor analysis. The findings show that Islamic ethical frameworks significantly strengthen institutional trust when systematically embedded in organizational structures. Organizations integrating Maqasid al-Shariah principles recorded 45% higher trust scores than conventionally managed institutions. Transparent zakat management, participatory decision-making, and value-based intermediation also improved stakeholder engagement. In conclusion, Islamic ethical frameworks function effectively as trust-building mechanisms when institutionalized through explicit governance structures, making moral economy a viable alternative to purely market-driven approaches.